The pulmonary vascular bed in patients with functionally univentricular physiology and a Fontan circulation. (11th August 2021) - Krimly, Ahmed; Jain, C. Charles; Egbe, Alexander; Alzahrani, Ahmed; Al Najashi, Khalid; Albert-Brotons, Dimpna; Veldtman, Gruschen R.
Abstract: Fontan palliation represents one of the most remarkable surgical advances in the management of individuals born with functionally univentricular physiology. The operation secures adult survival for all but a few with unfavourable anatomy and/or physiology. Inherent to the physiology is passive transpulmonary blood flow, which produces a vulnerability to adequate filling of the systemic ventricle at rest and during exertion. Similarly, the upstream effects of passive flow in the lungs are venous congestion and venous hypertension, especially marked during physical activity. The pulmonary vascular bed has emerged as a defining character on the stage of Fontan circulatory behaviour and clinical outcomes. Its pharmacologic regulation and anatomic rehabilitation therefore seem important strategic therapeutic targets. This review seeks to delineate the important aspects of pulmonary artery development and maturation in functionally univentricular physiology patients, pulmonary artery biology, pulmonary vascular reserve with exercise, and pulmonary artery morphologic and pharmacologic rehabilitation.